Van der Waals junction field effect transistors with both n- and p-channel transition metal dichalcogenides. (December 2018) - Lim, June; Kim, Minju; Jeong, Yeonsu; Ko, Kyeong; Yu, Sanghyuck; Shin, Hyung; Moon, Jae; Choi, Young; Yi, Yeonjin; Kim, Taekyeong; Im, Seongil
Abstract Two-dimensional (2D) transition metal dichalcogenides (TMDs)-based van der Waals (vdW) PN junctions have been used for heterojunction diodes, which basically utilize out-of-plane current across the junction interface. In fact, the same vdW PN junction structure can be utilized for another important device application, junction field effect transistors (JFETs), where in-plane current is possible along with 2D–2D heterojunction interface. Moreover, the 2D TMD-based JFET can use both p- and n-channel for low voltage operation, which might be its unique feature. Here we report vdW JFETs as an in-plane current device with heterojunction between semiconducting p- and n-TMDs. Since this vdW JFET would have low-density traps at the vdW interface unlike 2D TMD-based metal insulator semiconductor field effect transistors (MISFETs), little hysteresis of 0.0–0.1 V and best subthreshold swing of ~100 mV/dec were achieved. Easy saturation was observed either from n-channel or p-channel JFET as another advantage over 2D MISFETs, exhibiting early pinch-off at ~1 V. Operational gate voltage for threshold was near 0 V and our highest mobility reaches to ~>500 cm2 /V·s for n-channel JFET with MoS2 channel. For 1 V JFET operation, our best ON/OFF current ratio was observed to be ~104 . Electronics: MoS2 /MoTe2 junction field effect transistors Van der Waals heterostructures of atomically thin semiconductors enable junction field effect transistors (JFETs). A team led by Seongil Im at Yonsei University fabricated JFETs using a heterojunction of semiconductingp -MoTe2 (orp -WSe2 ) andn -MoS2 . Thep -type transition metal dichalcogenide (TMDC) works as a gate for then -type TMDC channel, whereas then -type TMDC operates as a gate for thep -type TMDC channel. Owing to the low density of traps at the van der Waals interface, the devices exhibit low hysteresis of 0.05–0.1 V and achieve a subthreshold swing of ~100 mV/decade. The highest mobility reaches 500 cm2 /V·s for then -channel JFET with MoS2, whereas thep -channel JFET with MoTe2 is characterized by a much lower mobility of ~13 cm2 /V·s. The highest ON/OFF current ratio was observed to be >104 .